170k views
1 vote
For the functions f(x) = 2x – 3 and g(x) = 5x + 5, find (f • g)(x).

1 Answer

6 votes

Answer:

f(g(x)) = 10x + 7

Explanation:

(f . g)(x) = f(g(x)) is the composition of the functions f(x) and g(x).

f(g(x)) means that g(x) becomes the input for f.

Now, f(x) = 2x - 3 and g(x) = 5x + 5.

f(g(x)) = f(5x + 5)

= 2((5x + 5) - 3)

= 10x + 10 - 3

= 10x + 7

f(g(x)) = 10x + 7 is the required answer.

User Yaniris
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.